Infrared spectrophotometry using thermal cameras for microfluidic systems (2021)
Analysis of a previously developed thermal camera, and modifications and implementations needed to turn it into an electronic hub. Development of a calibration methodology for thermal cameras for use in microfluidic systems as well as an ON/OFF controlled heaitng plate and calibrator cirucit prototype for thermal cameras.